Electrochemical Active Surface Area Determination of Iridium‐Based Mixed Oxides by Mercury Underpotential Deposition. Issue 18 (10th August 2021) - Duran, Silvia; Elmaalouf, Marine; Odziomek, Mateusz; Piquemal, Jean‐Yves; Faustini, Marco; Giraud, Marion; Peron, Jennifer; Tard, Cédric
Abstract: The electrochemical surface area (ECSA) is a critical property to describe, analyze and compare electrocatalysts. The determination of the mass activity of a given catalyst is associated with this parameter which can thus lead to materials benchmarking. Reliable and robust methods to measure ECSA are needed, and those have to accommodate different structures, morphologies and compositions. In this study, we investigate mercury underpotential deposition (HgUPD ) as a way to estimate ECSA for ultraporous electrocatalysts based on iridium and iridium‐molybdenum electrocatalysts for the oxygen evolution reaction. Results reveal a clear agreement between physisorption measurements and HgUPD with excellent reproducibility. The method shows also that pre‐ and post‐catalysis surface area measurements are not affected by the catalytic process on short timescale, opening the possibility of electrocalyst stability and degradation monitoring. Abstract : Material ultraporosity characterization : Mercury underpotential deposition (HgUPD ) was used to determine the electrochemical surface area (ECSA) of iridium and iridium‐molybdenum mixed oxides ultraporous materials. Comparison with physisorption measurements showed excellent agreement for a wide range of compositions and calcination temperatures.